How does the introduction of IFRS 17 impact the measurement of non-life insurance contracts? A case study - Nascimento, Daniela Paiva do (2022)
The new accounting standard for insurance contracts, IFRS 17, will become effective for accounting periods beginning on or after 1 January 2023. This dissertation aims to understand and assess the impacts that the introduction of this new standard has on the non-life insurance sector. This sector will mainly apply the Premium Allocation Approach (PAA). It is important to understand, how does the introduction of the discount in the measurement of the insurance liabilities affect the overall liabilities presented in the balance sheet? And the overall results of the entity? What is the relation between the risk adjustment (RA) (IFRS 17) and the implicit allowance for risk (IFRS4)? What is the impact of the introduction of a RA in terms of the financial statements? The research developed to answer these questions is exploratory and descriptive. The case study research method is the method used. The results show that the introduction of the discount leads to an increase in the insurance contract liabilities and consequently to a decrease in the equity and to a negative impact on the results disclosed. Regarding the interaction of the two variables, it was possible to conclude that when the risk adjustment is higher than the implicit allowance for risk, the liabilities are expected to be higher. On the other hand, the results are expected to be in line with the ones presented under the actual practice. If the opposite scenario occurs, the RA is lower than the implicit allowance for risk, the effects obtained are symmetric to the ones obtained before except for the results that tend to decrease in this scenario. Finally, regarding the introduction of the RA, the effects obtained showed that the liabilities are expected to increase and that the results follow the same tendency. The impacts of the introduction of IFRS 17 will depend on the actual practices of the entities. Therefore, the impacts are expected to be different from entity to entity.